(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2024)
Farmers need new technologies and information to cope with the challenges and difficulties of agricultural extension. YouTube, a low-cost tool, offers opportunities for farmers’ feedback, interaction, and networking. In order to utilize this tool for the benefit of farmers, it is necessary to learn the prospects and problems of YouTube and virtual video channels in agricultural content preparation and dissemination. Data were collected from 105 respondents under the Khulna Metropolitan Agriculture Office (both Metro 1 and 2) and from the 3 content creators from February to May 2023. However, the majority of respondents (94.30%) perceive YouTube as a promising tool for agricultural content dissemination. Besides, the majority of the respondents (64.80%) perceive problems with YouTube and virtual video channels in agricultural content dissemination. Age, farm size, experience, extension media contact, and training received positively impact respondents’ perceptions of YouTube. The findings suggest that the public extension system and policymakers may consider reducing internet costs and providing low-cost devices for both respondents and content creators. Additionally, other virtual video platforms like YouTube can be made more accessible, allowing audiences to access information from diversified virtual video channels. Int. J. Agril. Res. Innov. Tech. 13(2): 31-40, Dec 2023